2022
DOI: 10.1039/d2cc02517e
|View full text |Cite
|
Sign up to set email alerts
|

2,3-Diaminophenazine@carbon felt with chemical grafting via amide bonds as an electrode in lithium-ion batteries

Abstract: Grafting organic molecules onto insoluble matrix is an effective way to improve the electronic conductivity and insolubility in electrolyte of organic electrode materials. The active group of C=N in DAP@C...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Significantly, the peak at 1550 cm –1 is a combination of N–H deformation vibration and C–N of secondary amide stretching vibration while the peak at 1640 cm –1 is the stretching vibration bands of CO–NH. In addition, the XPS spectra in Figure S9a–d show that the peaks of Al 2p, Sr 3d, O 1s, and Si 2p are all observed in SAO-G@SiO 2 -LBA. Meanwhile, the peak at 402 eV in N 1s spectra and 288.1 eV in C 1s spectra can prove the formation of CO–NH. , Finally, the UV–vis results indicate that the concentration of lysozyme solution decreases after mixing with SAO-G@SiO 2 -LBA for 1 h (Figure S10). Combined with FT-IR, XPS, and UV–vis results, the LBA-functionalized SAO-G for LFP visualization is successfully prepared.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Significantly, the peak at 1550 cm –1 is a combination of N–H deformation vibration and C–N of secondary amide stretching vibration while the peak at 1640 cm –1 is the stretching vibration bands of CO–NH. In addition, the XPS spectra in Figure S9a–d show that the peaks of Al 2p, Sr 3d, O 1s, and Si 2p are all observed in SAO-G@SiO 2 -LBA. Meanwhile, the peak at 402 eV in N 1s spectra and 288.1 eV in C 1s spectra can prove the formation of CO–NH. , Finally, the UV–vis results indicate that the concentration of lysozyme solution decreases after mixing with SAO-G@SiO 2 -LBA for 1 h (Figure S10). Combined with FT-IR, XPS, and UV–vis results, the LBA-functionalized SAO-G for LFP visualization is successfully prepared.…”
Section: Resultsmentioning
confidence: 91%
“…Meanwhile, the peak at 402 eV in N 1s spectra and 288.1 eV in C 1s spectra can prove the formation of CO−NH. 66,67 Finally, the UV−vis results indicate that the concentration of lysozyme solution decreases after mixing with SAO-G@SiO 2 -LBA for 1 h (Figure S10). Combined with FT-IR, XPS, and UV−vis results, the LBA-functionalized SAO-G for LFP visualization is successfully prepared.…”
Section: Advanced Anticounterfeiting and Multiple Encryptionsmentioning
confidence: 99%
“…The reduction peak was at about 3.9 V, which can be attributed to the extraction of anions (the additional small reduction peak at around 4.1 V could be attributed to a two-step single-electron process). 44,45 Moreover, the difference between oxidation and reduction decreased after cycling, which indicated the smaller polarization and the easier storage after cycling and hence indicated that the initial stress of storage of large sized anions decreased, which should be ascribed to the possible activation process. 46,47 The CV curve became stable afterwards, indicating the reversibility of BDBDT electrodes.…”
mentioning
confidence: 98%